A Global Review Of Tax Morale: A Bibliometric Analysis For Future Research - Wicaksono, Galih; Sutopo, Bambang (WIM Solusi Prima, 2024)
This research aims to analyze the development and direction of research on tax morality globally, so that current and future publication trends can be identified. The issue of tax morale is interesting to study in more depth, because it supports increasing tax compliance and optimizing state revenues. This research uses a bibliometric approach, analysis via VOSviewer and Ms.excell, and is sourced from Scopus metadata from 2002 to 2024 with 248 publications. The results of the global analysis show that research on tax morality has increased significantly in the last four years in the form of English language journal articles, the subject area of which is mostly in the fields of economics and finance. This research is growing rapidly in Europe and America if we look at the composition of authors and their affiliations. Based on network analysis, the topic of tax morale is divided into five large clusters, namely: informal sector, tax compliance, tax system, tax evasion, and trust. Future research topics that can be further developed related to tax morality are related to social norms and tax reform. Meanwhile, keywords that researchers can link in the future are tax compliance with entrepreneurship and institutional theory, as well as tax avoidance with tax knowledge, social norms, corruption and trust. The limitation of this research is that it only comes from the Scopus database and the keywords are only focused on the word